Engagement of biotechnology in the protection of threatened plant species in Poland - Rybczyński, Jan J.; Mikuła, Anna (Biodiversity: Research and Conservation, 2006)
The paper summarizes the contribution of various biotechnological techniques to the protection of the Polish flora. Polish national programmes of wild plant conservation follow the international conventions on the conservation of nature and wildlife. Among the 2750 plant species of the Polish flora, only 296 are listed in the Polish Red Book, but the list of threatened and protected plants includes about 500 species. Biotechnology could serve as a tool for plant protection in various aspects, but the most important among them are: (i) vegetative propagation in vitro; and (ii) protection of the morphogenetic potential of cultured cells, tissues and organs. Extended subcultures and cryopreservation in particular ensure a high level of competence in long-term cultures. For dicotyledons, monocotyledons and ferns, some examples of various biotechnological methods used are presented and discussed.